2008
DOI: 10.1016/j.biopsych.2007.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Altered Vesicular Glutamate Transporter Expression in the Anterior Cingulate Cortex in Schizophrenia

Abstract: Background-Schizophrenia is a chronic, severe mental illness with profound emotional and economic burdens for those afflicted and their families. An increasing number of studies have found that schizophrenia is marked by dysregulation of glutamatergic neurotransmission. While numerous studies have found alterations of postsynaptic molecules in schizophrenia, a growing body of evidence implicates presynaptic factors. Vesicular glutamate transporters (VGLUTs) have been identified and are known to package glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 78 publications
2
74
1
Order By: Relevance
“…Regional differences in molecular abnormalities in schizophrenia are consistently reported in the literature (Katsel et al, 2005a, b;Kristiansen et al, 2006Kristiansen et al, , 2010Oni-Orisan et al, 2008), and although the sets of changes we found differed by cortical region, each set is functionally similar, resulting in decreased signal integration in both regions. This differential expression pattern may be inherent to the physiological circuits and inputs for each region.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regional differences in molecular abnormalities in schizophrenia are consistently reported in the literature (Katsel et al, 2005a, b;Kristiansen et al, 2006Kristiansen et al, , 2010Oni-Orisan et al, 2008), and although the sets of changes we found differed by cortical region, each set is functionally similar, resulting in decreased signal integration in both regions. This differential expression pattern may be inherent to the physiological circuits and inputs for each region.…”
Section: Discussionsupporting
confidence: 76%
“…Neuropathological examination revealed no neurodegenerative diseases including Alzheimer's disease in any subjects. Next of kin consent was obtained for each patient (Bauer et al, 2008(Bauer et al, , 2009(Bauer et al, , 2010Funk et al, 2009;Hammond et al, 2010;Oni-Orisan et al, 2008). Schizophrenia and comparison groups were matched for sex, age, pH, and PMI (Table 1).…”
Section: Tissue Acquisition and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy may be due to several factors. Our cohort was younger, racially mixed, and the tissue sample area may have come from different areas of the ACC than those used in the study of Oni-Orisan et al (2008). Glutamatergic terminals from cortex or thalamus contain vGLUT1 and vGLUT2, respectively (Fremeau et al, 2004), and are used to label the respective connections.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies of the ACC in SZ indicate numerous abnormalities (Todtenkopf et al, 2005;Oni-Orisan et al, 2008; for review see Fornito et al, 2009;Kraguljac et al, 2012a,b). Neurobiological differences between treatment response and treatment resistance in SZ are rarely studied in postmortem tissue, but provide a strategy for trying to link psychosis with particular neuropathology .…”
Section: Introductionmentioning
confidence: 99%